TIME MANAGEMENT SKILLS: COMPLETION OF STUDENT FINAL PROJECT DURING THE COVID-19 PANDEMIC - Putri, Shella Antoro; Mahmudah, Fitri Nur (UNIVERSITAS PAKUAN, 2021)
The covid-19 pandemic changed management to an unusual way. This has an impact on final year student activities. The purpose of this study was to determine the time management of final students in completing a thesis / scientific paper. The method used in this research is qualitative. The place where the research was carried out was in Yogyakarta where the participants were three final year students who were completing scientific papers and research. The data collection technique was done by interview and observation. The research procedure was carried out by means of Denzin Lincoln. Data analysis was performed using the Atlas.ti software version 8. The results of this study indicate that students in time management to complete the research as a graduation requirement require three things, namely planning, organizing, and implementing. These three management functions certainly have different indicators, where these indicators are the findings of this study. The results of this study were recommended by final year students who were doing research projects as a requirement for graduation. With good time management, it will be easier to do and solve it optimally and optimally.